Reader-Response Theory: Using Literary Works to Promote EFL Students Critical Reading Skills - Hamzah Puadi Ilyas; Ihsana El-Khuluqo; Wini Tarmini (Universitas Syiah Kuala, 2025)
This study investigated the combination of literary works and reader-response theory as a form of literary criticism to promote EFL students critical reading skills. To this end, 21 EFL students taking a reading course at a private university participated in the research. They were given five short stories in five sessions, read them, and responded to them based on reader-response theory. Oral and written responses were collected and analyzed to identify the elements of critical reading skills present. The study also distributed an open-response questionnaire to determine the processes students followed during reading activities. Thus, both the products (e.g., presentations, written responses, discussions) and processes of reading were investigated. The findings showed that five noticeable elements of critical reading emerged: reflecting, analyzing, interpreting, commenting, and reasoning. In addition, the activities had other benefits: students became involved in vocabulary acquisition and engaged with authentic materials. The study suggests that, apart from enhancing comprehension, reader-response theory and literary works can promote EFL students critical reading skills.